2017
DOI: 10.1155/2017/8964821
|View full text |Cite
|
Sign up to set email alerts
|

Present Status of Ganges River DolphinsPlatanista gangetica gangetica(Roxburgh, 1801) in the Turag River, Dhaka, Bangladesh

Abstract: Freshwater ecosystem degradation in the Turag River basin is increasing due to rising human settlement, reduced water flow during the dry season, new large land development projects, and toxic emissions caused by brick kilns. The population of river dolphins was estimated through surveys carried out from December 2012 to November 2013. Surveys were conducted on a fortnightly basis. The dolphins were counted within an 18.4 km stretch (known to be the most polluted stretch) of the 75 km long river. A total of 62… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 20 publications
1
13
0
Order By: Relevance
“…There are also significant occurrences in January. The seasonal patterns found in the present study are more or less similar to Baki et al (2017). These months are generally known to have heavy rainfall and the water level of the river and tributaries rises in Bangladesh.…”
supporting
confidence: 79%
See 1 more Smart Citation
“…There are also significant occurrences in January. The seasonal patterns found in the present study are more or less similar to Baki et al (2017). These months are generally known to have heavy rainfall and the water level of the river and tributaries rises in Bangladesh.…”
supporting
confidence: 79%
“…We found four sightings in three rivers (Turag, Buriganga, Dhaleswari) at Dhaka. Baki (2017) recorded 62 sightings in the Turag River from 2012-2023. In addition, two studies reported 29 and 34 sightings in 2003-2004 and 2012-2023 from the river Buriganga, respectively (Alam et al 2015, Alam & Sarker 2012.…”
mentioning
confidence: 99%
“…Moreover, this study also revealed that the increased severity of disasters and winter cold shock found to have a signi cant effect on the socio-economic status (poverty status) of the studied population living in the Southern coastal belt of Bangladesh. Consequently, all these things force the coastal shermen to seek loans, others' mercy dependency, and favors from others like moneylenders (GO/NGOs) or Mahajans, who compel them to sell/mortgage their land, imposing advanced labor selling, cash crops in exchange for returning the money borrowed or lent 34,[40][41][42]50 . Ultimately, the shermen always remain in debt and borrow money from various sources to replenish their nancial crisis [40][41][42] and are trapped in a vicious cycle of poverty 34,42 .…”
Section: Discussionmentioning
confidence: 99%
“…There are more than 700 rivers in the country including tributes that flow through the country, the capital city of Bangladesh is one of the megacities in the world and it was established 400 years ago. This city was started in the northern part of the Buriganga River which was called at that time (the Ganges River) [1] . The capital city of Bangladesh is spread over an area of 1.5 to 1.7 kilometers square close to the connection of the Postogola and Buriganga Rivers) [2] .…”
Section: Introductionmentioning
confidence: 99%
“…In the last years, the Buriganga River was going a very dangerous situation which led to being the most polluted river in Bangladesh, the main factors of this pollution are anthropogenic [12] and some other natural factors, many types of research said that main problem of the river is the rapid growth of Dhaka city, the industrial revolution, population density, and climate change, the combination of these factors caused Buriganga river to be more polluted than other rivers [4] . Many researchers proposed different sources but still, there is a variation in their findings, like the number of waste spilled into the river every day [13] , percentages of each waste, the role of society in keeping the safety of the river, legislation of the river safety, management of the river, So, these different results caused frustrate to understand specific factors causing the adverse situation of the Buriganga River, also it's tough to present the health status of the people living surrounding area of the river, the water quality of the river may change from months to months, year to year due to amount of waste entering the river [1] so it is needed to be tested every time to assess the current status of the river, Like Bangladesh Water pollution also become a severe problem in Malaysia and Philippine. Specially Kualalampur and Manila, the capital city of Malaysia and Philippine respectively.…”
Section: Introductionmentioning
confidence: 99%